Analysis of the Implementation of a Fingerprint-Based Biometric Attendance System in Improving Employee Discipline at the Muko-Muko Bathin VII Sub-district Office - Pratiwi, Yuriski; Hidayat, Rahmat; Putranto Riau , Dwi (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to analyze the implementation of a fingerprint-based biometric attendance system and its impact on employee discipline at the Muko-Muko Bathin VII Sub-district Office, Bungo Regency. In today's digital era, the use of technology in human resource management is increasingly important to improve efficiency and accountability. The method used in this study is a mixed methods approach, which combines quantitative and qualitative analysis to provide a comprehensive picture of the effectiveness of the attendance system. Data were collected through questionnaires distributed to employees, in-depth interviews with management, and direct observation of the attendance process. The results of the study indicate that the implementation of a fingerprint attendance system provides convenience in recording attendance and increases the accuracy of employee attendance data, thus supporting better human resource management. However, challenges such as lack of employee understanding of the importance of discipline and technical problems in using the system are still obstacles to its implementation. Routine evaluation of the system and training for employees are needed to improve the effectiveness of the implementation of this system. This research is expected to contribute to the development of employee management policies and the application of technology in government agencies, as well as to encourage increased employee discipline and productivity. Thus, this research does not only focus on the technical aspects of the biometric attendance system, but also considers human factors that influence the success of the application of the technology. It is expected that the results of this study can be a reference for other agencies in implementing similar systems and improving the quality of employee management.